(untitled) (KULT_online, 2023)
Emotions matter. This is true for much in our lives, but it is just as vital for accessing, understanding, and using heritage. In Emotional Heritage, Laurajane Smith presents revealing insights into this assumption and gives further substance to a gradual, yet often inchoate, people- and affect-oriented shift in the heritage field. Analyzing an extensive set of empirical data compiled over three continents and several years, the renowned critical heritage scholar emphasizes the importance of addressing the emotional dimension of heritage genuinely and comprehensively in all heritage agendas.